Synthesis, characterization and Antimicrobial activity of Schiff base ligand and Metal complexes (Indian Journal of Chemistry (IJC), 2024)
This study describes the synthesis of a new Quinoline Schiff base by condensation of 3-formyl-2-hydroxyquinoline-5-carbonitrile and 1-tosylhydrazine. After preparing Schiff base, metal complexes were formed using Cu(II), Ni(II), and Co(II). FT-IR, 1H NMR, 13C NMR, ESI-MS, UV-Visible, XRD, spectroscopy were all able to demonstrate the full synthesis of Schiff base and associated metal complexes. Preparations of compounds with low conductivity were found to be non-electrolytic. The ligand has O, N, and O binding sites, according to the FT-IR data. According to the magnetic moment of the compounds, the metal complexes of Cu(II), Ni(II), and Co(II) are paramagnetic. The compounds were tested for their properties against Bacillus subtilis, Escherichia coli, and Candida albicans. It has been found that Metal (II) complexes have potent antibacterial and antifungal action in comparison to ciprofloxacin and ketoconazole.